Neutrino flares from black hole coronae - Vieyro, Florencia Laura (2011)
We present a model for neutrino flares in accreting black holes based on the injection of a non-thermal population of relativistic particles in a magnetized corona. The most important products of hadronic and photohadronic interactions at high energies are pions. Charged pions decay into muons and neutrinos; muons also decay yielding neutrinos. Taking into account these effects, coupled transport equations are solved for all species of particles and the neutrino production is estimated for the case of accreting galactic black holes.